TINJAUAN YURIDIS TERKAIT PENERAPAN AMBANG BATAS PENCALONAN PRESIDEN DALAM PEMILIHAN UMUM DI INDONESIA (UNDANG UNDANG NOMOR 7 TAHUN 2017) - Anwar, Misbakhul; Fahrazi, Mahfudz (Universitas Islam Kadiri, 2023)
After the amendment to the constitution, the election of the president and vice president was directly elected by the people. In the election, there is a presidential threshold norm which is considered to violate constitution norms and limit people’s rights in election. In this research, the authors used normative legal research methods. This research explained that the presidential threshold was first applied to the Presidential Election in 2004. In the 2009, 2014, 2019 presidential elections there was an increase in the presidential threshold. The application of the presidential threshold in the Presidential Election causes a legal disagreement between the Constitution and the Electoral Act. Article 6A Section 2 of the Constitution actually lists the threshold for presidential candidacy but the legislature added a certain percentage. In simultaneous elections between the presidential election and the election of members of representative institutions, the application of the presidential threshold becomes irrelevant. The application of the presidential threshold is irrelevant to be applied in a country that adheres to a presidential system. The reason is that the President immediately gets a mandate from the people. So that the application of the presidential threshold can lead to a parliamentary system.